ECUADORIAN VARIANT OF SPANISH: FUTURE TENSE INSTEAD OF IMPERATIVE - Syzko, Mariia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article is devoted to studying the peculiarities of the Ecuadorian variant of the Spanish language, namely the unusual way of forming imperatives using the simple future tense. From the beginning, the Spanish language in Ecuador coexisted with other national languages of indigenous peoples, particularly Kichwa or Quechua. As a result of their semantic-pragmatic and syntactic convergence, Ecuadorian Spanish acquired new characteristics that distinguish it from the rest of the national variants. One of these features is using the simple future tense as an imperative. We determined that the future form is used to soften orders, requests, and recommendations; at the same time, it also has other contextual meanings, such as remoteness in time, transfer of responsibility, emphasis, and highlighting the importance of the enouncement. It is unusual how the structure characteristic of the imperative mood is transferred to the imperative formed with the help of the future tense, namely the adding of the “se” particle and pronouns of the direct object after the verb in the future simple tense.__________References:• Albor, H. «‘Da’ + gerundio, ¿un quechuismo? y otras maneras de atenuar los imperativos.» Hogo Albor. (1973): 316–318.• Briz Gómez, A. Al hilo del español hablado. Reflexiones sobre pragmática y español coloquial (Sevilla: Editorial Universidad de Sevilla, 2018), 241.• Gutiérrez Marrone, N. «Estudio preliminar de la infl uencia del quechua en el español estándar de Cochabamba, Bolivia.» Dialectología hispanoamericana: estudios actuales (1980): 58–93.• Haboud, M., Palacios, A. «Imperatividad y atenuación en el castellano andino ecuatoriano.» Lengua y Sociedad en el Mundo Hispánico 37 (2017): 21–54.• La nueva política lingüística panhispánica [Електронний ресурс] // ASALE, Real Academia Española. – 2004. – Режим доступу до ресурсу: https://www.rae.es/la-institucion/politica-panhispanica.• Lara, L. F. «Por una redefinición de la lexicografía hispánica.» Nueva Revista de Filología Hispánica 44 (1996): 345–364, https://www.jstor.org/stable/40299438• Niño-Murcia, M. Construcciones verbales del español andino: interacción quechua-española en la frontera colombo-ecuatoriana (University of Michigan, 1988).• Toscano, Mateus. H. «El español en el Ecuador.» Revista de Filología Española, anejo LXI (1953), https://doi.org/10.24201/nrfh.v9i4.1304.• Yépez, L. M. Empleo del Futuro de Indicativo como Imperativo en el Español de Quito (Mariana – Quito, 1984).
Keywords: Ecuadorian variant of the Spanish language, imperative, future tense, Kichwa